Profil Literasi Fisika Siswa Madrasah Terhadap Mitigasi Bencana Erosi Batang Sinamar - Zakwandi, Rizki; Rochman, Chaerul; Nasrudin, Dindin; Yuningsih, Endah Kurnia; Putra, Sandijal (Sekolah Tinggi agama Islam Negeri (STAIN) Curup, 2018)
Contextual physics learning with natural phenomena in the environment will be more meaningful for learners. One of the learning contexts that can be raised is the phenomenon of soil erosion in the river Batang Sinamar, West Sumatra. This study aims to describe the profile of physics literacy ability of learners about the erosion of river wall of Batang Sinamar in District of Lima Puluh City of West Sumatera Province. The method used is pre-experimental with one shoot test design. Data collection is done by disseminating instrument literacy consisting of four questions about the process, concept, context and best attitude of learners in response to the phenomenon. The results showed that there were significant differences in literacy ability of physics concepts between students attending school near the erosion site and students who went to school away from the erosion site. The average overall grade of the learners at the closest school is 2.66 and the furthest school is 2.14. The results of this study can be used as the initial reference in the preparation of enrichment materials about the physical matter related to the phenomenon of erosion of the Sinamar rod wall.